STUDENTS’ PERSPECTIVE TO IMPROVE VOCABULARY ENGLISH SPEAKING CLASS BY USING BUBBLE APPLICATION AS LEARNING MEDIA - Sri Ayu Fatmawati; Benni Ichsanda Rahman Hz (Teaching English and Language Learning English Journal, 2025)
Artificial Intelligence (AI)-based learning is currently developing rapidly, in improving students' speaking skills with vocabulary, influency, and pronunciation. Research shows that the use of AI can produce better academic results by providing support in overcoming specific learning gaps. The focus of this study is that Bubble Application can improve students' speaking skills by using vocabulary in the application. This study aims to activate the improvement of the Bubble application in the class students' English speaking skills. 28 students participated, 28 of whom have answered the questionnaire given by the researcher and 10 students were interviewed by the researcher, to support the existing questionnaire. This study used a qualitative method in the form of descriptive questionnaires and interviews to analyze students' perceptions of the Bubble application in improving students' English speaking. The Bubble app can improve students' speaking skills by expanding their knowledge of new vocabulary that they know and use in their daily conversations. Furthermore, the app also provides example sentences by teaching students how to pronounce them, thus improving their ability to communicate appropriately. Furthermore, the audio in the application can make students listen to the correct pronunciation and can be done repeatedly, thus practicing students' speaking skills. Thus, this study can provide insight into the development of other educational applications to continue to transmit and adjust their features to better meet user needs. Keywords: Artificial Intelligence (AI), Bubble Aplication Effectiveness,Improve Student, Improvement of english,Speaking skill,